2023
DOI: 10.1002/admi.202300144
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Ferrofluid‐Wrapped Drops: Translation, Coalescence, and Release

Abstract: Magnetic manipulation of droplets has emerged as a promising strategy to achieve several complex tasks ranging from targeted drug delivery and micro‐robotics to controlled chemical synthesis. Hence, proper control in creating magnetically responsive droplets is indispensable for successful implementation. Here, an impact‐based encapsulation technique is employed to create stable ferrofluid‐wrapped single‐liquid and compound droplets inside a water bath. Thereafter, a permanent magnet is used to manipulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The film thickness reduces after continuous draining, and the van der Waals force comes into play, resulting in the rupture of the thin film and the merging of the two droplets. It can be mentioned that the drainage of the ferrofluid film at the point of contact (of two drops) can be controlled using a strong magnetic field, as observed in one of our works . The experimental video corresponding to the coalescence of DI water and the EG drop can be found in the Supporting Information (Movie S3).…”
Section: Results and Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The film thickness reduces after continuous draining, and the van der Waals force comes into play, resulting in the rupture of the thin film and the merging of the two droplets. It can be mentioned that the drainage of the ferrofluid film at the point of contact (of two drops) can be controlled using a strong magnetic field, as observed in one of our works . The experimental video corresponding to the coalescence of DI water and the EG drop can be found in the Supporting Information (Movie S3).…”
Section: Results and Discussionmentioning
confidence: 55%
“…It can be mentioned that the drainage of the ferrofluid film at the point of contact (of two drops) can be controlled using a strong magnetic field, as observed in one of our works. 40 The experimental video corresponding to the coalescence of DI water and the EG drop can be found in the Supporting Information (Movie S3). Based on this demonstration, we have performed proof-of-concept experiments to demonstrate the microchemical reactions depicted in the next section.…”
Section: Coalescence Of Liquid Drops On the Mrssmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial collection of scholarly work has previously been reported on the interfacial dynamics and its characterization of ferrofluid droplets. Guo et al focused on examining the impact of magnetic fields on ferrofluid droplets positioned on a modified hydrophobic surface. They observed that the presence of superhydrophobic surfaces enhances the mobility of ferrofluid droplets as a result of their reduced surface energy and restricted adhesion.…”
Section: Introductionmentioning
confidence: 99%